The Reports of the Russian Empire Officials on the Semirechye Region: A Historiographic Analysis - Kuketova, Aigerim A.; Shayakhmetov, Nurbek U.; Shashaev, Auezhan K.; Musabalina, Gulnara T.; Kushenova, Ganizhamal I. (International Journal of Criminology and Sociology, 2022)
The paper describes the process of scientific substantiation of the Russian Empire’s preliminary preparation for the colonisation of the Kazakh steppes in the second half of the 19th century. The purpose of the paper is to analyse the political, as well as the economic situation (development of animal husbandry and agriculture) in the Semirechye region based on sources compiled with the help of the works of military officials of 19th century tsarist Russia. The paper also provides an assessment and comparative analysis of the subjective characteristics of historical sources on the region development. Considering the study of the region until the end of the 19th century, the authors have found that Semirechye was of interest for the Russian Empire in terms of the presence of important natural resources. Based on the methods of scientific research, we also identified the relationship between the ethnographic, political and economic development of the region. In general, the paper shows the importance of the reports of military officials as valuable primary sources of information.